(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
Bahasa Melayu and bahasa Indonesia, the official languages of Malaysia and Indonesia respectively, are both derived from the Malay language. A common romanized spelling system was adopted by both languages and has been in use since 1972. Nevertheless, there are still differences in the romanized spelling of Arabic loanwords affecting both languages. Discrepancies in spelling between the two languages may be attributed to the conventions of the Jawi script in the spelling of Arabic loanwords, which cannot be accurately transcribed in the Latin alphabet. Ultimately, the conventions of the Jawi script, particularly in the Malay language in Malaysia, is more evident than in the Malay language of Indonesia. The comparison reveals that the Malay-speaking community in Malaysia is more positively inclined and more likely to accept Islamic tradition than the Malay-speaking community in Indonesia. Keywords: common romanized spelling, Jawi script, bahasa Melayu, bahasa Indonesia, orthography